Merubah Karakter Positif Siswa Dengan Model Quantum Teaching - Ainiah Rahmah Fadli; Taufina Taufina; Zuardi Zuardi (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The aim of this study is to describe the alteration of positive characteristic of the students with learning implementation  by using  Quantum Teaching model. The type of this study is qualitative approach. Teacher and students in sixth grades is determined the subject in this research which account at 15 subjects. The result of the research depict that there are alteration from students with negative characteristic to positive characteristic. The positive characteristic that have been obtained was self honesty and self confient. After utilizing Quantum Teaching model by the teachers, the students who used to had negative characteristic alter to the students with possitive characteristic which is portrayed confident self and honesty toward themselves. Keywords:, Positive Characteristic, Quantum Teaching Model.